TEXTUAL ENHANCEMENT: THE EFFICACY OF PROMOTING NOUN PHRASE ACQUISITION - Mira Shartika; Mazroatul Ishlahiyah (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study investigated the improvement of students' abilities in identifying forms of noun phrases through textual enhancement, the difference in results between the high and low achievers in identifying forms of noun phrases through textual enhancement, and the relationship between textual enhancement and the ability of students who have high and low grades in identifying forms of noun phrases. The quantitative design was applied in order to obtain information. The project involved 44 EFL learners taking Intermediate English Grammar subject in one of Islamic universities in Malang, Indonesia. The participants were divided into 2 classes consisting of high and low achievers. The high achievers were the experiment group, and the low achievers were the control group. The results revealed that there was significant difference in the students’ achievement in noun phrase acquisition between those who were taught by using textual enhancement (experimental group) and those who were taught by not using textual enhancement (control group). Second, there was significant different achievement between the high achievers and the low achievers of control and experimental group in learning noun phrase. Finally, there was an interaction found between Textual Enhancement (TE) and students’ initial abilities (high achievers and low achievers).